Mitigation of Greenhouse Gas Emissions from Rice Production - Sander, Björn Ole (International Rice Research Institute, 2022)
Presented to the meeting of the Council for Partnership on Rice Research in Asia (CORRA) on October 2022, the slides discuss rice fields as emission source, mitigation options, and Monitoring, Reporting and Verification of greenhouse gas emissions in agriculture.